The effects of different industrial sugars on royal jelly production - Karlidag, S.; Koseman, A.; Akyol, A.; Yil, G.; Seker, I.; Uyumlu, A. B.; Erdogan, S. (Hellenic Veterinary Medical Soc, 2022)
In this study, the larval acceptance rate and the royal jelly yield in honeybee (Apis mellifera L.) colonies supplemented with different industrial sugars at different locations were determined. For this purpose, feeding groups (1. Sucrose group, 2. Glucose group, 3. Bee feed syrup group, 4. Control group) and locations (1. Battalgazi, 2. Dogansehir) were formed. In queenless colonies that produce royal jelly, in order to sustain 5-15 day-old young feeder worker bees, two sealed frames with brood from support colonies were added. The royal jelly yield was harvested seven times. Based on the location, the feeding groups, and the location x feeding groups interaction, 12600 larvae were grafted, 9054 larvae were accepted, and the larval acceptance rate was determined as 71.86%. Based on the location, feeding groups and the location x feeding group interaction, the yield per cell was calculated as 213.15 +/- 11.53 mg/ cell, the yield per colony as 6.88 +/- 0.38 g/app., and the total yield per colony as 34.40 +/- 1.91 g/colony. In the study, no statistically significant difference was determined between feeding with sucrose, bee feed and the supplementary feeding with glucose. On the other hand, it was determined that the location where the royal jelly was produced affected both the larval acceptance and the royal jelly yield.
Keywords: Royal jelly; Bee feed; Honeybee (Apis mellifera L.); Feeding; Sugar